Diseño y Construcción de un Prototipo Automatizado para Asistir el Barrido del Transductor del Equipo Olympus OMNI SCAN MX en la Inspección de Soldadura por Ultrasonido en Tuberías. (2024)
The present work aims to design and build the prototype of an automated mechanism applied to the Olympus OMNI SCAN MX equipment transducer to assist the sweeping in the ultrasonic inspection of welding in pipes. The prototype behaves as an accessory that can be adapted to the equipment used in CMS Engineering and Projects. This will be able to move around the pipe while constantly maintaining the distance and speed to the weld bead, known as Skip Distance. The device was designed for 6" pipes. The prototype will be developed in 4 phases, including the design of the fixed and mobile components and the control used for movement